Excavations of the Taman Detachment of the Bosporan Expedition of IHMC RAS in 2014–2018 - Kashaev, Sergey (Hyperboreus, 2019)
A survey of the excavations of the necropolis of the site Artyushchenko-2 conducted by the Taman Department of the Bosporan expedition of the Institute for the History of Material Culture (RAS) in 2014–2018.